Effectiveness of Discovery Learning-Based Speaking Skills Using Animated Videos - Errine Vira Febiola; Mukmin Mukmin; Kemas Muhammad; Achmad Yani (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
Mastery of Arabic speaking skills (maharah kalam) remains difficult for senior madrasah students, particularly when Instruction relies heavily on conventional methods with limited interactive media. This study investigates the effectiveness of Discovery Learning supported by animated video media at MA Babussalam Payaraman. Employing a quantitative approach with a pretest–posttest control group design, data were collected through tests, questionnaires, observations, and interviews, and analyzed using descriptive statistics, normality and homogeneity tests, and an independent sample t-test. Results show a substantial improvement in the experimental class, with scores increasing from 55% in the pretest to 84.56% in the posttest, while the control class rose only from 49.34% to 68.69%. Students taught with animated videos also demonstrated greater engagement, motivation, and confidence.The study concludes that Discovery Learning, combined with animated video media, effectively enhances Arabic speaking skills. Its primary contribution lies in proving that integrating process-oriented learning with dynamic visual media significantly boosts communicative competence and learner participation, offering a more impactful alternative to traditional Arabic language teaching.